SISTEM APLIKASI UJIAN BERBASIS LOCAL AREA NETWORK (LAN) PADA SMA SWAKARYA BINJAI - Triono, Arif; Dewi, Sintia; Fauzi, Achmad; Sihombing, Anton (Majalah Ilmiah Kaputama, 2018)
One of the routine activities undertaken to as an evaluation tool to assess how much ability and understanding and skills that have been obtained by the students is to conduct exams. In Conventional , exam requires paper stationery items and devices. In addition , the conventional exam vulnerable to fraud and requires teachers to correct students' answers .For reasons of efficiency , it can be built by using the online exam application Local Area Network ( LAN ) . The application consists of two , namely the application server ( for administrators and teachers ) and the client   (for students ) . Under this system , admin ( head or deputy principals ) determine the schedule of exams and teachers to enter the exam through an application server . Then , the students answer exam questions through the client application . Problem is sent from the application server to the client , the first randomized sequence, so that each student will get about random sequence .Then , the students answer exam questions through the client application . Problem is sent from the application server to the client , the first randomized sequence, so that each student will get about random sequence .